2011
DOI: 10.1111/j.2044-8287.2011.02027.x
|View full text |Cite
|
Sign up to set email alerts
|

How do young adults perceive the risk of chlamydia infection? A qualitative study

Abstract: Objectives. This study aimed to improve understanding of how young UK genito‐urinary medicine (GUM) patients perceive the risk of chlamydia, and identify implications for health education.Design. A qualitative methodology was chosen.Methods. Semi‐structured interviews with 27 respondents aged 16–22 years old were conducted. Data were subjected to thematic analysis.Results. Respondents made assessments of the perceived seriousness of, and their personal susceptibility to, chlamydia infection. Judgements about s… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4

Citation Types

2
23
0

Year Published

2013
2013
2021
2021

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 22 publications
(26 citation statements)
references
References 19 publications
2
23
0
Order By: Relevance
“…This disparity may primarily be due to the differences in age and educational levels of the samples, and the different methods of data collection. The present study found that whilst most people knew STIs could cause infertility in females, awareness of the effect on male fertility was lower, which is in concordance with the literature [26,27]. We found no clear gender differences in level of understanding.…”
Section: Discussionsupporting
confidence: 91%
See 2 more Smart Citations
“…This disparity may primarily be due to the differences in age and educational levels of the samples, and the different methods of data collection. The present study found that whilst most people knew STIs could cause infertility in females, awareness of the effect on male fertility was lower, which is in concordance with the literature [26,27]. We found no clear gender differences in level of understanding.…”
Section: Discussionsupporting
confidence: 91%
“…Previous research has demonstrated that young people have a poor awareness of the link between STIs and infertility [19,23,24] whereas others have reported the opposite [25-27]. This disparity may primarily be due to the differences in age and educational levels of the samples, and the different methods of data collection.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…This study shows that one way to significantly increase the intention and the intention-predicting variables to screen is giving informational invitation letters. Moreover, assuming that low susceptibility is the cause of a low intention, more research is needed on whether there is a discrepancy between perceived susceptibility and real susceptibility and what the possible reasons for this discrepancy are [27]. …”
Section: Discussionmentioning
confidence: 99%
“…Adolescents’ self-perceived risk of C. trachomatis infection may be influenced by its mostly asymptomatic course,5 limited personal experience of STIs, wrong beliefs due to lack of specific knowledge,6 and by the influence of alcohol and drugs while making sexual decisions 7. Subjective invulnerability and an optimistic bias related to one's own sexual health may alter personal risk perception 2 8–10.…”
mentioning
confidence: 99%